Palindrome in the sequence of the ribosomal peptidyl transferase center suggests a protoribosome emergence scheme - Ilana Agmon; Yair Shimony (Proceedings of the National Academy of Sciences, 2026)
The emergence of a simple version of the modern ribosome represents an indispensable step in the evolution of life as we know it. Standalone dimeric protoribosome models, derived from the peptidyl transferase center of the modern ribosome, have been shown to perform the primary ribosomal function of catalyzing peptide bond formation. However, the likelihood of the random occurrence of a suitable 70-mer RNA strand capable of serving as the monomer sequence remains questionable. Here, what initially appeared to be a “hallucinatory” AlphaFold3 prediction of a putative protoribosome, was found to express the presence of a palindrome spanning most of the ribosome-derived monomer sequence. The framework of this sequence suggests a simple, experimentally testable molecular mechanism by which an analog of the ribosome-derived protoribosome could have self-assembled from a few copies and complementary strands of a single 10-mer RNA segment. This scenario significantly reduces the complexity attributed to the autonomous emergence of a protoribosome and provides a plausible starting point for a continuous evolutionary pathway, leading from inanimate matter to life as we know it.